Just-in-Accuracy: Mobile Approach to Uncertainty - Ceberio, Martine; Lauter, Christoph; Kreinovich, Vladik (Journal of Mobile Multimedia, 2024)
To make a mobile device last longer, we need to limit computations to a bare minimum. One way to do that, in complex control and decision making problems, is to limit precision with which we do computations, i.e., limit the number of bits in the numbers’ representation. A problem is that often, we do not know with what precision should we do computations to get the desired accuracy of the result. What we propose is to first do computations with very low precision, then, based on these computations, estimate what precision is needed to achieve the given accuracy, and then perform computations with this precision.